ChemInform Abstract: Catalytic and Atom‐Economic Intermolecular Amidoselenenylation of Alkenes. Issue 22 (12th May 2016) - Tang, E.; Wang, Weilin; Zhao, Yinjiao; Zhang, Meng; Dai, Xin
Abstract: A broad range of alkenes, such as 1‐substituted, 1, 1‐disubstituted as well as (E)‐ and (Z)‐1, 2‐disubstituted olefins, including cyclic derivatives, react with N‐(phenylseleno)phthalimide to form amidoselenides in generally high yields and with high regio‐ and diastereoselectivities.